Swedish - Finnish word lists, various domains - Swedish-Finnish Word List, Several Domains - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish-Sweden Finnish word list with words from several domains: society, labour market, higher education, nature, culture, etc. Approx. 3,000 entries. 1981-2014.

Svensk-sverigefinska ordlistor, flera olika domäner. 1980 - 2016.
Svensk - finska ordlistor, flera domäner - Svensk-finska ordlistor, flera domäner
Keywords: Dictionary, Polyglot; Flerspråkig ordbok som ämne; Linguistics; Språkvetenskap; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik; Studies of Specific Languages; Studier av enskilda språk